Implementasi ISAK 35 Dalam Penyusunan Laporan Keuangan Sektor Pendidikan - Raniwihati, Septia; Djasuli, Mohamad (Politeknik Negeri Ambon, 2024)
Educational institutions are non-profit organizations whose aim is not to make a profit. A good financial report is of course a financial report that is based on financial accounting standards, ISAK 35 is the standard used to prepare non-profit oriented financial reports. This research aims to determine the preparation of financial reports in accordance with ISAK 35. This research produces five reports, namely a comprehensive income report, a report on changes in net assets, a financial position report, a cash flow report, and notes to financial reports. The data analysis method used is descriptive qualitative. Data collection techniques are carried out through interviews, observation and documentation. The types of data in this research are primary data and secondary data. The results of the research carried out explained that the Sigma Cakery SMKN X business unit had not implemented ISAK 35 in recording its financial reports. The report prepared by the Sigma Cakery SMKN X business unit only records cash in and cash out. Financial reports presented in accordance with ISAK 35 will produce more detailed financial reports.